Community Service through Assistance in Establishing a Waste Bank in Simbur Naik Village, East Tanjung Jabung Regency, Jambi Province - Fatriani, Riri Maria; Beriansyah, Alva; Lega, Michael; Rohayati, Wahyu; Putra, Dinda Syufradian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Waste banks are important for sustainable waste management as they allow people to trade their waste for money or useful items, reducing pollution and increasing awareness about recycling and waste management. Simbur Naik Village was selected as a service location due to its potential for receiving waste from other areas and the low public awareness about environmental protection. The village government collaborated with Universitas Jambi and TPBIS Omah Sinau Jambi to establish the waste bank. The service involved initial education and discussions to raise community awareness about the environment, followed by assistance in establishing the waste bank through cooperation agreements and memorandums of understanding. The evaluation of the service showed that village officials and participants fully supported the discussion process and the formation of the waste bank. The goal is to create a clean, healthy environment and manage waste wisely.